Floriculture New Crop Update - Report from California Pack Trials 2003 - Rick Schoellhorn; Alexis A. Richardson (EDIS, 2005)
Pack trials are industry events held in early April each year highlighting the new releases in flowering crops for each year. This is an industry event and, generally, not open to the public. Most of the exhibiting companies are not familiar names to the average consumer because by the time the plant is sold at a retail nursery it is tagged by the nursery that produces it, not by the breeder company that created or released the plant. For that reason consumers should use the name of the plant when looking to buy plants listed here, while nurseries should contact their distributors and use the company name to get the correct source. This document is ENH899, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 16, 2005.